2007
DOI: 10.1074/jbc.m702657200
|View full text |Cite
|
Sign up to set email alerts
|

Mitofusin-2 Is a Major Determinant of Oxidative Stress-mediated Heart Muscle Cell Apoptosis

Abstract: An inexorable loss of terminally differentiated heart muscle cells is a crucial causal factor for heart failure. Here, we have provided several lines of evidence to demonstrate that mitofusin-2 (Mfn-2; also called hyperplasia suppressor gene), a member of the mitofusin family, is a major determinant of oxidative stress-mediated cardiomyocyte apoptosis. First, oxidative stress with H 2 O 2 led to concurrent increases in Mfn-2 expression and apoptosis in cultured neonatal rat cardiomyocytes. Second, overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
128
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(137 citation statements)
references
References 43 publications
7
128
2
Order By: Relevance
“…Similar studies have reported the effective use of siRNAs to knockdown both Nox and Mfn2 and inhibit ROS production and apoptosis in cardiac cells, including HL‐1 cardiomyocytes (Yeh et al, 2011), H9c2 cardiomyocytes, (Shen et al, 2007), cultured neonatal rat cardiomyocytes (Papanicolaou et al, 2011) and mouse ventricular cells (Moe et al, 2011). However, while this investigation found no changes in apoptosis in DOX‐treated HL‐1 cardiomyocytes in the presence of Nox2 or Mfn2 knockdown, it is possible that efficacy of transfection may have influenced the measured endpoint.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Similar studies have reported the effective use of siRNAs to knockdown both Nox and Mfn2 and inhibit ROS production and apoptosis in cardiac cells, including HL‐1 cardiomyocytes (Yeh et al, 2011), H9c2 cardiomyocytes, (Shen et al, 2007), cultured neonatal rat cardiomyocytes (Papanicolaou et al, 2011) and mouse ventricular cells (Moe et al, 2011). However, while this investigation found no changes in apoptosis in DOX‐treated HL‐1 cardiomyocytes in the presence of Nox2 or Mfn2 knockdown, it is possible that efficacy of transfection may have influenced the measured endpoint.…”
Section: Discussionmentioning
confidence: 71%
“…In agreement, a considerable number of studies identified in the Ingenuity Knowledge Base were found to support the idea that increased Mfn2 in cardiomyocytes predicted an adverse outcome, promoting cell death through apoptotic mechanisms. For example, Shen et al (2007) demonstrated that Mfn2 mediates oxidative stress‐induced apoptotic cell death in neonatal cardiomyocytes. Additionally, siRNA inhibition of Mfn2 prevented oxidative stress‐induced apoptotic cell death in H9c2 cardiomyocytes (Karbowski et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…HUVECs were pretreated with APS for 4 h and then treated with the indicated concentrations of TNF-α for 24 h. All assays were performed in triplicate. The cells were incubated with 0.5 mg/mL 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenylterazolium bromide for 4 h, and the absorbance at 490 nm was measured, as described previously [14] . The MTT kit was purchased from Roche Applied Science (Indianapolis, Indiana).…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Hoechst 33342 staining Nuclear fragmentation was detected by incubating fixed cells (70% alcohol and 30% acetone) in 10 mmol/L Hoechst 33342, as previously described [15] . A total of 500-700 cells in 10 randomly chosen fields from each dish were counted to determine the percentage of apoptotic nuclei.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…Since ERK activation has been shown to mediate induction of apoptosis (Cheung and Slack 2004), Mfn2 may protect cells by inhibiting ERK signaling independent of Mfn2 mitochondrial fusion activity. Two recent studies have shown that overexpression of Mfn2 in heart muscle cells (Shen et al 2007) or vascular smooth muscle cells (Guo et al 2007) induces apoptosis through inhibition of Ras-PI3K-Akt signaling. Here, Mfn2 is suggested to act in a pro-apoptotic manner.…”
Section: Mitofusins and Apoptosismentioning
confidence: 99%